2021
DOI: 10.1093/jrr/rraa105
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from conducting disease monitoring in low-dose exposure conditions as a counter-measure after a nuclear disaster

Abstract: The complex disaster of the Great East Japan Earthquake and the Fukushima nuclear accident caused concern about their various health impacts. Many types of intervention are desired as a countermeasure, depending on the phase of the disaster cycle. The importance of developing and applying codes of conduct has recently been emphasized for post-disaster investigations. Thyroid examination as a type of cancer screening survey was launched from October 2011 after the Fukushima nuclear accident as part of the Fukus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Four rounds of the thyroid ultrasound examination have been conducted in Fukushima Prefecture over the past 10 years, and a fifth round of opt-out screening is progressing despite these global trends. This examination has resulted in more than 200 thyroid cancer diagnoses (116 in the first round, 70 in the second, and 31 in the third) [ 20 ]. The observed age-specific prevalence of thyroid cancer was more than 30 times the expected rate in the first round, based on previous cancer registry data showing rates before screening [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four rounds of the thyroid ultrasound examination have been conducted in Fukushima Prefecture over the past 10 years, and a fifth round of opt-out screening is progressing despite these global trends. This examination has resulted in more than 200 thyroid cancer diagnoses (116 in the first round, 70 in the second, and 31 in the third) [ 20 ]. The observed age-specific prevalence of thyroid cancer was more than 30 times the expected rate in the first round, based on previous cancer registry data showing rates before screening [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, four rounds of the thyroid ultrasound examination have been conducted in Fukushima over the past 10 years, and a fth round with opt-out style screening is progressing despite these global trends. This examination has resulted in more than 200 thyroid cancer diagnoses (116 in the rst round, 70 in the second, and 31 in the third) [15]. The United Nations Scienti c Committee (UNSCEAR) concluded that the signi cant increase among screening participants relative to that expected was because of overdiagnosis and not the result of low radiation dose exposure [5].…”
Section: Introductionmentioning
confidence: 99%